IDENTIFICATION OF CULTIVATION MANAGEMENT AND ABIOTIC COMPONENTS IN PEOPLE’S NUTMEG PLANTATIONS IN SOUTH ACEH REGENCY - Afrillah, Muhammad; Muslimah, Yuliatul; Lizmah, Sumeinika Fitria; Junita, Dewi; Harahap, Evi Julianita (RADJA PUBLIKA, 2024)
Nutmeg is the leading commodity of South Aceh plantations. Cultivation management and environmental factors have an impact for optimal production. The aim of this research is to identify management and abiotic components in people's nutmeg plantations in South Aceh Regency. The methods used are interviews and direct observation on nutmeg plantation using purposive sampling to collect data of abiotic components. Location was recommended by Department Agriculture of Aceh Selaan Regency. The research parameters consist of management aspects of nutmeg cultivation and abiotic components. The results show that the average nutmeg land area is ≤1 ha, the planting pattern is agroforestry, and the planting distance is 5 x 5 m. The nutmeg seeds used are sourced from farmers' own propagation through generative propagation. On average, 50.66% of farmers do not fertilize, while the rest fertilize using NPK fertilizer (42.68%) in a spread at a dose of 1 kg/plant, and around 6% use organic fertilizer. The altitude ranges from 2.6-27.2 meters above sea level, the light intensity is 207.6-832.6 cd, the temperature is between 27.8oC-30.9 oC, and the humidity is 61-80%. The pH value is between 6.8-7, soil water content 21.78-65.52%, Nitrogent 0.10-0.43%, Phosfor 0.48-19.35, and Kalium 0.26-2.75%. In conclusion, the management of nutmeg cultivation in South Aceh Regency is still not optimal, such as planting distance, fertilization and seeding. Meanwhile, from the abiotic environmental aspect, such as light, soil pH and humidity are suitable for the growth of nutmeg. Agroforestry effects of water content and NPK elements in nutmeg plantations.